Phoma identification manual. Differentiation of specific and infra-specific taxa in culture - Boerema, G. H.; Boerema, G. H.; Gruyter, J. de; Gruyter, J. de; Hamers, M. E. C.; Hamers, M. E. C.; Noordeloos, M. E.; Noordeloos, M. E. (Wallingford :CABI Publishing, 2004)
This book is a practical manual to aid identification of Phoma species, and will be useful for researchers working in the areas of mycology, plant pathology and microbiology. It provides line drawings and keys for the identification of 223 specific and infraspecific taxa of Phoma, including common pathogenic and saprophytic species, with references to additional diagnostic literature, representative cultures and documentation of the numerous synonyms formerly used in the mycological and phytopathological literature. Methods for identification and differentiation of species in vitro are covered, then species are described under the following sections: Phoma, Heterospora, Paraphoma, Peyronellaea, Phyllostictoides, Sclerophomella, Plenodomus, Macrospora, Pilosa and miscellaneous.
Keywords: FF610 - Viral, Bacterial and Fungal Diseases of Plants, (New March 2000); ZZ333 - Microbial Ecology, (New March 2000); ZZ380 - Taxonomy and Evolution; ZZ392 - Morphology of Microorganisms, (New March 2000); ZZ396 - Microbial Life Cycles, (New March 2000)